How did we find out about microwaves? - Asimov, Isaac, 1920-1992.; Kors, Erika W. (New York : Walker, 1989)
Describes the discovery of microwaves and explains how they function and their many uses.
Includes index.
4-6
Young Adult
Keywords: Microwaves -- Juvenile literature; Microwaves; Microwaves